2019
DOI: 10.3390/en12173235
|View full text |Cite
|
Sign up to set email alerts
|

Hot Metal Temperature Prediction at Basic-Lined Oxygen Furnace (BOF) Converter Using IR Thermometry and Forecasting Techniques

Abstract: In oxygen steelmaking, the charge calculation strongly depends on hot metal temperature prediction. Although a hot metal temperature drop from the blast furnace in a steel plant may be too complex to be accurately modeled in detail, the combined use of sensors and statistical models can improve temperature estimation and result in better cost, quality and productivity, as well as lower emissions. In order to develop a simple but robust method for hot metal temperature forecasting, the suitability of infrared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 27 publications
1
16
1
1
Order By: Relevance
“…In a previous modelling work, time series were applied to solve this problem. It was shown that the introduction of exogenous predictors into an auto-regressive integral moving average (ARIMA) model improved its performance [21]. Conversely, the potential benefit of introducing the L last observations of the predicted variable as input variables will be analyzed in the present work.…”
Section: Backward Phasementioning
confidence: 96%
See 4 more Smart Citations
“…In a previous modelling work, time series were applied to solve this problem. It was shown that the introduction of exogenous predictors into an auto-regressive integral moving average (ARIMA) model improved its performance [21]. Conversely, the potential benefit of introducing the L last observations of the predicted variable as input variables will be analyzed in the present work.…”
Section: Backward Phasementioning
confidence: 96%
“…Since the hot metal pouring may extend over a significant period of time, there is not a clear time limit between torpedo and ladle. Considering that the heat losses in torpedoes and ladles were found to be similar [21], both holding times can be grouped together without excessive simplification.…”
Section: Explanatory Variablesmentioning
confidence: 99%
See 3 more Smart Citations